Clinical Ethics for Consultation Practice - Bertino, Joseph T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides a robust analysis of the history of clinical ethics, the philosophical theories that support its practice, and the practical institutional criteria needed to become a practicing clinical ethicist. Featuring cases and a step-by-step approach, this book combines knowledge points associated with moral philosophy and medicine with general skill objectives for ethics consultants. The book aids in developing analytic moral reasoning skills for clinical ethicists, fostering the comprehensive education and professional development of clinical ethics consultants. In addition, it offers key components of how an ethics consultation curriculum manifest in an educational venue for clinical ethicists are illustrated. Adaptable and relevant for educating multiple disciplines in health care, this resource enables ethicists to understand the philosophical foundations and practical application of clinical ethics.
1. A Philosophical Justification for Normative Ethics in Clinical Ethics and Medicine -- 2. Methods & Standards of Clinical Ethics Consultation -- 3. Moral Reasoning, Ethics Facilitation & Virtue -- 4. Organizational Ethics and Residency Requirements for Clinical Ethics Consultation -- 5. Concluding Remarks.
Keywords: Medical Ethics; Medical education; Bioethics; Medical laws and legislation; Medical Ethics; Medical Education; Bioethics; Medical Law; Ethics, Medical